Comparing the effectiveness of different approaches to raise awareness about antimicrobial resistance in farmers and veterinarians of India - Sharma, Garima; Mutua, Florence K.; Deka, Ram Pratim; Shome, R.; Bandyopadhyay, S.; Shome, B.R.; Kumar, N.G.; Grace, Delia; Dey, Tushar K.; Lindahl, Johanna F. (2022)
Objective The purpose of this study was to raise awareness and knowledge about AMR and antibiotic use among dairy farmers, paravets (veterinary assistants), and veterinarians. Different methodologies were investigated, and knowledge changes were measured. Materials and methods The study was conducted in September-December of 2018 in four states of India. It had two parts, intervention part (September-October 2018) and follow-up survey (November-December 2018). The villages were randomly allocated to either one of the three intervention approaches (1-classic AMR; 2-animal health; 3-animal health plus AMR) or to be a control. A follow up survey was done to assess the effect of interventions. Results In total, 274 dairy farmers and 51 veterinary professionals (21 veterinarians and 30 paravets) participated in the follow up survey. 69% of the dairy farmers and 84% veterinary professionals were a part of the intervention survey before. The average knowledge score in farmers was 7.8.It was found that the knowledge score was higher in farmers who had participated in earlier focus group discussions (p<0.05), had received intervention in approach 2 (animal health, p=0.03), or approach 3 (animal health plus AMR, p=0.01), and were females (p=0.03). Conclusion Our study identified that most of the people who participated in the discussions in the intervention stage showed an improvement in the awareness levels. The veterinary professionals had good knowledge but lacked the interest in training the farmers about antimicrobial resistance. Regular awareness programs must be conducted for the dairy farmers to increase knowledge about antibiotics and avoid inappropriate use. Also, the veterinary professionals should be given frequent trainings on how to make the farmers understand leading to a behavioural change.